PENGARUH DOSIS PUPUK KANDANG AYAM YANG DIBERIKAN DENGAN CARA YANG BERBEDA TERHADAP SIFAT TANAH DAN HASIL TANAMAN SELADA (Lactuca sativa L.) DI MEDIA GAMBUT - Arif Hidayat; Ervina Aryanti; Yusmar Mahmud (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2021)
Manure is a fertilizer derived from animal manure, which can improve the structure of peat soil and provide nutrients for lettuce plants (Lactuca sativa L.). Peat soil is a type of soil that has many obstacles in cultivation including acidic pH, low nutrient availability such as N, P, and K. Manure can be used in solid and liquid forms. This study aims to determine the dosage and the appropriate way of giving chicken manure to the yield of lettuce and the nature of the soil after being given chicken manure. This research has been carried out from April to June 2018 on experimental land, Agronomy Laboratory. This study used a Completely Randomized Design (CRD) with 7 treatments namely without fertilizer application (control), 37.5 g solid fertilizer of chicken manure, 75 g solid fertilizer of chicken manure, 112.5 g solid fertilizer of chicken manure, 37.5 g of solid fertilizer thawed chicken manure,75 g of solid fertilizer thawed chicken manure, 112.5 g of solid fertilizer thawed chicken manure. The results showed that 112.5 g solid manure from chicken manure was the appropriate dose to increase the growth of lettuce plants, namely plant height (15.48 cm), leaf width (11.60 cm), number of leaves (11.00 strands), weight plant (37.83 g), weight root plant (3.48 g), and increasing the total N content of the soil (0.40%).